2016
DOI: 10.1242/dmm.025999
|View full text |Cite
|
Sign up to set email alerts
|

Early applications of granulocyte colony-stimulating factor (G-CSF) can stabilize the blood-optic nerve barrier and further ameliorate optic nerve inflammation in a rat model of anterior ischemic optic neuropathy (rAION)

Abstract: Granulocyte colony-stimulating factor (G-CSF) was reported to have a neuroprotective effect in a rat model of anterior ischemic optic neuropathy (rAION model). However, the therapeutic window and anti-inflammatory effects of G-CSF in a rAION model have yet to be elucidated. Thus, this study aimed to determine the therapeutic window of G-CSF and investigate the mechanisms of G-CSF via regulation of optic nerve (ON) inflammation in a rAION model. Rats were treated with G-CSF on day 0, 1, 2 or 7 post-rAION induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(104 citation statements)
references
References 44 publications
10
92
0
2
Order By: Relevance
“…Neuroinflammation has been shown to play a vital role after optic nerve ischemia [28][29][30][31]. In our observations, treatment with astaxanthin decreased the levels of IL-1β and TNFα in the retina and reduced ED1-positive macrophage infiltration in the optic nerve after rAION induction.…”
Section: Discussionsupporting
confidence: 63%
“…Neuroinflammation has been shown to play a vital role after optic nerve ischemia [28][29][30][31]. In our observations, treatment with astaxanthin decreased the levels of IL-1β and TNFα in the retina and reduced ED1-positive macrophage infiltration in the optic nerve after rAION induction.…”
Section: Discussionsupporting
confidence: 63%
“…[9][10][11][12] After the induction of ON ischemia, the breakdown of the blood-optic nerve barrier (BOB) occurs within hours, 8,13 and the recruitment of extrinsic macrophages and the activation of resident microglia at the ischemic core are identified as early as 3 days after the insult. [14][15][16][17] Functional changes such as in the amplitude of visual-evoked potentials (VEPs) were also mitigated early before the permanent degradation following rAION induction. 18 There is evidence suggesting that the administration of corticosteroids can effectively decrease tissue edema by increasing the expression levels of the occludin and claudin-5 genes and stabilizing the blood-brain barrier (BBB) in models of brain osmotic insult, as well as models of retinal diseases.…”
Section: N Onarteritic Anterior Ischemic Optic Neuropathy (Na-aion)mentioning
confidence: 99%
“…The laser settings were the same as that reported in our previous paper. 14,27,28 Flash Visual-Evoked Potentials (FVEP)…”
Section: Raion Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second study, Rong-Kung Tsai and co-authors aimed to determine the therapeutic window and anti-inflammatory mechanism for the neuroprotective effect of granulocyte colony-stimulating factor (G-CSF), using an established rat model of acute ischemic optic neuropathy. They showed that early treatment with G-CSF rescued visual function and retinal ganglion cell survival, most likely through stabilising the blood–brain barrier and reducing macrophage infiltration (Wen et al, 2016). …”
Section: Original Research Contributions: the Uniqueness Of The Rat Mmentioning
confidence: 99%